Prosocial Behaviour and Mental Well-being of Higher Secondary School Students - PANDEY, PRANAY; MOHANTY, PRAGYAN (JOURNAL OF INDIAN EDUCATION, 2025)
This study explores the correlation between prosocial behaviour and mental well-being among higher secondary school students, aiming to understand how acts like helping, sharing and cooperating influence the psychological health of individuals in this pivotal developmental stage. It seeks to assess the levels of prosocial behaviour and mental well-being among higher secondary school students while examining the disparities across various categorical variables, such as gender, school location and academic stream. A sample of 200 Government-aided higher secondary school students aged between 15 to 18 years participated in the study, drawn from North and South 24 Parganas districts of West Bengal. Employing a survey methodology, the study utilised two scales, i.e., Prosocial Behaviour Scale and the Mental Well-being Scale developed by the researchers themselves. The study revealed significant disparities in prosocial behaviour based on gender and school location as well as variations in mental well-being concerning these factors. Crucially, the research uncovered a statistically significant positive correlation between prosocial behaviour and mental well-being among higher secondary school students, highlighting the importance of fostering prosocial behaviours to enhance students’ psychological health.